Analysis of the Level of Awareness and Implementation of Sustainable Development Goals (SDGs) in MSMEs in Supporting Economic Growth - Hikmah Indri Yani Harahap; Tuti Anggraini; Nurlaila Nurlaila (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
MSMEs play a vital role in the Indonesian economy, yet their awareness and implementation of the SDGs remain poorly understood. This study emphasizes the importance of understanding and implementing the SDGs to enhance sustainable economic progress for micro-enterprises. The method used was a qualitative case study, designed to gain in-depth insight into the real-world situations faced by micro-enterprises. Information was collected through semi-structured discussions with MSME stakeholders and relevant individuals. The findings indicate that understanding and implementation of the SDGs among micro-enterprises are suboptimal and still face various obstacles, influenced by a lack of knowledge, limited access to information, and a lack of resources. However, the implementation of SDG principles promises to improve business performance, enhance competitiveness, and facilitate economic growth for MSMEs if supported by education, mentoring, and the integration of sustainability principles into business management